Parliamentary Hearings as a Form of Public Discussion - Asatryan, Artak (Bulletin of Yerevan University C: Jurisprudence, 2024)
Parliamentary hearings, as an important platform for the discussion of public issues, contribute to the participation of broad layers of the public in deciding on various issues of state importance. This format becomes even more important when legal drafts that received a great public interest appear on the agenda. Therefore, the proper legal regulation of this institution acquires special importance. Within the framework of this article, reference was made to the legal regulations for the organization and conduct of parliamentary hearings, along with which the foreign experience regarding a number of issues was also presented. In particular, among others, issues related to entities with the authority to call parliamentary hearings, submitting applications for participation in parliamentary hearings, the incomplete determination of the powers of the officials authorized to conduct the parliamentary hearings, summarizing the parliamentary hearings, drawing up the relevant minutes and publishing them on the website of the parliament, the importance of remote participation in parliamentary hearings and the lack of legal regulation of such participation were also discussed. As a result of the analysis, a number of proposals have been made to eliminate and fill in the shortcomings and gaps, which will contribute to the further improvement of this important institution.